(untitled) (Eurasian Medical Research Periodical, 2023)
The high prevalence and incidence of schizophrenia, the severity of clinical manifestations, often leading to profound disability, high economic costs, labor losses and social damage associated with this disease are the reason that the problem of schizophrenia remains one of the most urgent in modern clinical and social psychiatry